2016
DOI: 10.1007/s00431-016-2747-1
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab is not a “magic drug” in post-transplant recurrence of nephrotic syndrome

Abstract: Pediatric patients with end-stage renal failure due to severe drug-resistant nephrotic syndrome are at risk of rapid recurrence after renal transplantation. Treatment options include plasmapheresis, high-dose of cyclosporine A/methylprednisolone and more recently—rituximab (anti-B CD20 monoclonal depleting antibody). We report five patients with immediate (1–2 days) post-transplant recurrence of nephrotic syndrome, treated with this kind of combined therapy including 2–4 weekly doses of 375 mg/m2 of rituximab.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Then, we reviewed full-text of selected articles and removed 49 studies because the topics were not relevant to the subject. Finally, 17 investigations were included in the systematic review (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The flow diagram of study selection is shown in Figure 1.…”
Section: Search Results and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we reviewed full-text of selected articles and removed 49 studies because the topics were not relevant to the subject. Finally, 17 investigations were included in the systematic review (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The flow diagram of study selection is shown in Figure 1.…”
Section: Search Results and Characteristicsmentioning
confidence: 99%
“…Continued decrease the use of immunosuppressants and steroid. Only one study concluded that RTX might not be effective in all pediatric cases of rapid post-transplant recurrence of NS, and they suggested that before deciding to use this protocol, the ratio of benefit to risk should carefully be balanced on an individual basis (10). In this systematic review, 17 studied were included, but only two of them were randomized clinical trials (most of them were retrospective studies without control groups), hence we could not do a quantitative synthesis (metaanalysis).…”
Section: Neutropenia=1mentioning
confidence: 99%
“…Rituximab has been reported to be effective in SRNS, although not in our patient, as proteinuria was only slightly decreased, and this was in association with IAds. Prior reports have also indicated that rituximab is not always successful with post‐transplantation recurrence of SRNS …”
Section: Discussionmentioning
confidence: 99%
“…Prior reports have also indicated that rituximab is not always successful with post-transplantation recurrence of SRNS. 10 Abatacept, which is an inhibitor of the T-cell costimulatory molecule B7-1, has led to a complete remission in some rituximab-resistant post-transplantation NS. 11 IAds were stopped for our patient during the abatacept infusions, although it soon became apparent that the proteinuria increased and reached nephrotic levels, thus confirming IAds-dependency.…”
Section: Discussionmentioning
confidence: 99%
“…To hamper this process, an anti-CD20 B cell depleting monoclonal antibody, rituximab, has been introduced as immunosuppressive treatment for transplanted patients. Despite the fact that the use of this drug has increased patients' survival, it fails to induce chronic unresponsiveness to the graft [39, 40]. One of the possible reasons underneath may be that plasmablasts and plasma cells, two key players in chronic rejection, do not express CD20 on their cell surface.…”
Section: Potential Role Of Regulatory B Cells In Transplantationmentioning
confidence: 99%